Brain Metabolism of Allopregnanolone and Isoallopregnanolone in Male Rat Brain - Öfverman, Charlotte; Hill, Martin; Johansson, Maja; Bäckström, Torbjörn (International journal of molecular sciences, 2025)
Allopregnanolone (allo) and isoallopregnanolone (isoallo) are neuroactive steroid epimers that differ in hydroxyl orientation at carbon three. Allo is a potent GABA-A receptor agonist, while isoallo acts as an antagonist, influencing brain function through their interconversion. Their metabolism varies across brain regions due to enzyme distribution, with AKR1C1–AKR1C3 active in the brain and AKR1C4 restricted to the liver. In rats, AKR1C9 (liver) and AKR1C14 (intestine) perform similar roles. Beyond AKR1Cs, HSD17Bs regulate steroid balance, with HSD17B6 active in the liver, thyroid, and lung, while HSD17B10, a mitochondrial enzyme, influences metabolism in high-energy tissues. Our current data obtained using the GC-MS/MS platform show that allo and isoallo in rats undergo significant metabolic conversion, suggesting a regulatory role in neurosteroid action. High allo levels following isoallo injection indicate brain interconversion, while isoallo clears more slowly from blood and undergoes extensive conjugation. Metabolite patterns differ between brain and plasma—allo injection leads to 5α-DHP and isoallo production, whereas isoallo treatment primarily yields allo. Human plasma contains mostly sulfate/glucuronided steroids (2.4–6% non-sulfate/glucuronided), whereas male rats exhibit much higher free steroid levels (29–56%), likely due to the absence of zona reticularis. These findings highlight tissue-specific enzymatic differences, which may impact neurosteroid regulation and CNS disorders.